2020
DOI: 10.25134/erjee.v9i1.3784
|View full text |Cite
|
Sign up to set email alerts
|

Five language style analysis of the host in the tonight show talk show: A sociolinguistics analysis

Abstract: This thesis presents the language style used by Jimmy Fallon in The Tonight Show talk show. The objective of this study is to investigate the types of language style used by Jimmy Fallon in his talk show based on Joos’s (1967) theory. This research applied descriptive qualitative method. The data of this research were taken from the talk show video and the video transcript. The main theory which was used in this research was taken from Five O’clock book by Martin Joss (1976) and the book of An Introduction to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
0
0
Order By: Relevance
“…Another study analyzed language styles employed by Jimmy Fallon in his show. The results indicated that 29 conversations contained style about Joos's theory, with casual style being the dominant one (Muziatun, 2020). Advertising language helps advertisers reach the target audience and affects consumers' purchasing attitudes (Akinbode, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another study analyzed language styles employed by Jimmy Fallon in his show. The results indicated that 29 conversations contained style about Joos's theory, with casual style being the dominant one (Muziatun, 2020). Advertising language helps advertisers reach the target audience and affects consumers' purchasing attitudes (Akinbode, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%